(untitled) (Research, Society and Development, 2023)
Introduction: The impact caused by the pandemic of COVID-19 on the dimensions of eating behavior of the general population during home confinement should be analyzed in order to understand the damage caused in this regard. Aim: To verify the impact of the COVID-19 pandemic on the dimensions of eating behavior of the general population during home confinement. Method: Integrative review, From the establishment of the research keywords, it was performed the crossing of descriptors "Pandemic/Pandemic"; "Binge eating/Eating compulsion"; "Covid-19"; "Coronavirus/Coronavirus"; "Eating disorders/Eating Disorders" in the following databases: Health Library (BVS), National of Medicine (PubMed MEDLINE), Scientific Eletronic Library Online (SCIELO), EbscoHost and Google Scholar. Results: Forty-two articles were found in the Health Library (VHL), National of Medicine (PubMed MEDLINE), EbscoHost and Google Scholar databases, from which the published titles and abstracts were read. After careful reading of the publications, 30 articles were not used due to the exclusion criteria. Thus, 12 articles, all in English, were selected for final analysis and construction of the literature review on the theme. Conclusion: Based on the literature review presented, it can be concluded that the conditions caused by the pandemic caused changes in eating habits that, together with sedentary lifestyle, socioeconomic condition and emotional instability favor the emergence of eating disorders. With the advent of social isolation, it is evident that the eating habits were harmed.